2001
DOI: 10.1177/089033440101700406
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Exclusive Breastfeeding in Ibadan, Nigeria

Abstract: Although nationwide efforts to promote exclusive breastfeeding began in Nigeria in 1992, data on this type of infant feeding are still generally scarce. Current status breastfeeding data were obtained from 2794 mothers, enrolled from randomly selected infant welfare clinics in Ibadan, Nigeria, to evaluate factors that are associated with exclusive breastfeeding. The exclusive breastfeeding rate dropped from 57.4% at 1 month to 23.4% at 6 months. Using multiple regression analysis, younger age of infant (P < .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
42
4
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 10 publications
10
42
4
7
Order By: Relevance
“…Similar results have been reported in a study in Nigeria (Lawoyin et al, 2001). As primiparous mothers have no previous experience with breastfeeding, it is important to target this group in breastfeeding promotion and support programmes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have been reported in a study in Nigeria (Lawoyin et al, 2001). As primiparous mothers have no previous experience with breastfeeding, it is important to target this group in breastfeeding promotion and support programmes.…”
Section: Discussionsupporting
confidence: 87%
“…In Timor-Leste, older mothers (X35 years) were less likely to exclusively breastfeed their infants than younger mothers. However, most previous studies in both developed and developing countries have found increased breastfeeding performance with higher maternal age after appropriate adjustment for confounders (Lawoyin et al, 2001;Dubois and Girard, 2003). The lower rates of exclusive breastfeeding with female infants compared to males warrants further investigation to understand the sociocultural factors leading to this gender difference in infant feeding practices.…”
Section: Discussionmentioning
confidence: 90%
“…30 From the information available in three of the reviewed studies, the rate of exclusive breastfeeding decreases as infant"s age increases. [30][31][32] Onah, Osuorah, Ebenebe, Ezechukwu, Ekwochi, Ndukwu found a relationship between exclusive breastfeeding and maternal educational level, socioeconomic status and the mode of delivery. 19 According to this study, mothers who had a caesarean section and mothers with high socioeconomic status were less likely to practice exclusive breastfeeding.…”
Section: Description Of Reviewed Papers and Sample Characteristicsmentioning
confidence: 94%
“…[22][23][24][25] Only two studies reported that the WHO definitions were used in estimating breastfeeding rates, 19,21 although five other studies defined exclusive and/or other types of breastfeeding correctly. 26,31,32,40,44 Exclusive breastfeeding…”
Section: Description Of Reviewed Papers and Sample Characteristicsmentioning
confidence: 99%
“…70,82 These habits have been correlated with a higher prevalence of ECC. 82 The duration of breastfeeding and exclusive breastfeeding is longer in women from upper social classes, in those who are better educated, [83][84][85] in older mothers and in those with a steady relationship 52 and, dental hygiene is also more appropriate in this group 12,39 in opposition to underprivileged classes, in which ECC is more common. Early introduction of foods, the use of baby bottles and preference for sugary foods are more frequently observed in underprivileged classes.…”
Section: Breastfeeding Versus Ecc: Reasons and Counterargumentsmentioning
confidence: 99%